Modification of hempseed protein isolate using a novel two-stage method applying high-pressure homogenization coupled with high-intensity ultrasound - Ruyu Zhang; Wangang Zhang; Xuan Dong; Meng Wai Woo; Siew Young Quek (Ultrasonics Sonochemistry)
Hempseed protein isolate (HPI), a novel plant protein, possesses advantages as an alternative food protein from a nutritional and sustainable perspective. This study investigated HPI modification by examining the effects of high-pressure homogenization combined with high-intensity ultrasound (HPH + HIU) on the physicochemical and functionality of HPI. Firstly, the optimal homogenization pressure (180 MPa) was selected based on the solubility and particle size of HPI. Then, the effect of ultrasonic treatment time (2, 5, and 10 min) was studied at the optimal homogenization pressure. The results showed increased solubility of HPI after all treatments. Particularly, the HPH + HIU2min treatment had a synergistic effect that maximumly increased the solubility of HPI from 6.88 % to 22.89 % at neutral pH. This treatment significantly decreased the HPI’s particle size, β-sheet and total sulfhydryl contents while maximizing the random coil level, intrinsic fluorescence intensity and surface hydrophobicity compared to the single HPH or HIU2min treatments. The protein structure was modified and unfolded, enhancing the water-protein and oil-protein interactions, as reflected in the increase in water and oil absorption, foaming and emulsifying properties. However, extending the ultrasonic time to 5 min for the HPH + HIU treatment increased protein particle size and weakened the functional properties of HPI. Further prolonging the ultrasonic time to 10 min partially loosened the protein aggregates and restored the functional properties of HPI to some extent. The findings indicate a promising application of HPH + HIU as an efficient way for HPI modification to facilitate its broader application in the food industry.